A study on the determinants affecting Crude Palm Oil (CPO) price in Malaysia / Nadhirah Muhammad Fithal - Muhammad Fithal, Nadhirah (Faculty of Business and Management, 2018)
There are many factors that may affect the changes of crude palm oil prices in Malaysia. In this studies, however analyzes the influence of Brent Crude oil and also price of substitutes which are olive oil price, soybean oil price and sunflower oil price that act as an independent variable while crude palm oil act as a dependent variable. Needless to say the price of commodity very fluctuates. Rapid development of the country makes a huge demand and supply around the world. Thus, this study will brief more about the relationship between independent variables and price of crude palm oil in Malaysia. The data obtained to conduct this study was collected in yearly basis from year 1988 to 2017. In the process of findings, there are few types of analysis were tested using the Econometric Views (E-Views) such as Multiple Linear Regressions, normality test, unit root tests and more. Based on the result, it reveals that the price of olive oil and price of sunflower oil is negatively insignificant influence towards crude palm oil price. Brent crude oil shows negative relationship with price of crude palm oil but have significant. Meanwhile, only soybean oil price have positive correlation towards price of crude palm oil in Malaysia. Therefore, it is perfectly significant influence on fluctuation price of crude palm oil.